Peran Analisis Jabatan dalam Meningkatkan Kinerja dan Efisiensi Tenaga Pendidik : Sebuah Kajian Literatur - Gesha Ayu Hanafiah; Intan Nurlaili Thoyyibah; Muslimatul Afiyah; Ayu Rita Risky Rani; Bela Aprilia Putri; Eka Putrilhia; Mu’alimin Mu’alimin (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Job analysis plays a crucial role in improving the performance and efficiency of educators. This study aims to examine the role of job analysis in the context of education through a literature review approach, focusing on five selected articles published between 2020 and 2024. The findings indicate that proper job analysis can enhance teacher performance by ensuring their placement aligns with qualifications, identifying training needs, and clarifying tasks and responsibilities. Additionally, the integration of organizational culture and regular updates to job analysis contribute to work efficiency and educator productivity. These findings provide practical implications for educational institutions to optimize human resource management through dynamic and structured job analysis. ,